2018
DOI: 10.17116/oftalma201882217-29
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative fluorescence diagnostics in surgery of intracranial meningiomas: analysis of 101 cases

Abstract: Meningioma is a well fluorescent tumor, with the technique sensitivity being 94.1%. In some cases, the use of fluorescence diagnostics in surgery of meningiomas improves identification of residual tumor fragments and enables correction of a surgical approach. To assess the effect of fluorescence diagnostics on the recurrence rate and disease-free duration, further research is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…Although high-grade gliomas usually emit high levels of fluorescence, low-grade gliomas show a relatively lower amount of fluorescence after 5-ALA administration 20 . In addition, unlike in high-grade gliomas, PpIX fluorescence is reported to be patchy or lacking in some metastases 21 and central nervous system lymphomas 22 and rarely in meningiomas 23 25 as visualized with the blue light of current operating microscopes. Visual PpIX fluorescence in gliomas is not uniform and is typically patchy with areas of high and low fluorescence intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Although high-grade gliomas usually emit high levels of fluorescence, low-grade gliomas show a relatively lower amount of fluorescence after 5-ALA administration 20 . In addition, unlike in high-grade gliomas, PpIX fluorescence is reported to be patchy or lacking in some metastases 21 and central nervous system lymphomas 22 and rarely in meningiomas 23 25 as visualized with the blue light of current operating microscopes. Visual PpIX fluorescence in gliomas is not uniform and is typically patchy with areas of high and low fluorescence intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, residual tumor tissue might remain undetected during meningioma surgery and result in local tumor recurrence. Recently, 5-ALA fluorescence was also described as a promising marker for intraoperative visualization of intracranial meningiomas apart from the main indication of HGG [14,16,20]. In this sense, Kajimoto et al [21] published the first series of 24 meningioma patients in 2007 and observed visible 5-ALA fluorescence during surgery in 83% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, 5-ALA fluorescence was also applied in other tumors than HGG for improved intraoperative identification of anaplastic foci, various tumors in stereotactic biopsies, spinal tumors, brain metastases and meningiomas [8][9][10][11][12][13][14][15]. In meningiomas, visible 5-ALA fluorescence of the tumor bulk during meningioma surgery was reported in a recent series in 77-94% of patients [14][15][16]. According to first observations, 5-ALA fluorescence was found to be useful to visualize also peritumoral tissue such as infiltrated bone flaps and satellite lesions [14].…”
Section: Introductionmentioning
confidence: 99%
“…The results of 5-ALA application in adults with different types of brain tumors were highlighted in detail in our earlier publications (18, 18, 21, 26). In this study, fluorescence sensitivity in the treatment of high-grade gliomas was 90.2% ( n = 238/264), which corresponded to findings of other authors (22, 3234).…”
Section: Discussionmentioning
confidence: 77%
“…At the end of 90-ies first data on the potential use of 5-ALA in neurosurgery appeared, with first publications being devoted to malignant gliomas (1, 22). Today, 5-ALA is applied in surgery of different types of brain and spinal cord tumors for both adults and children, including meningiomas (37, 2628), metastasis (811), neurocytomas (12), ependymomas (13, 14), medulloblastomas (15).…”
Section: Discussionmentioning
confidence: 99%